Analisis Kinerja Keuangan Dalam Menilai Kesehatan Koperasi Di Koperasi Al-Ikhlas - Martiani S, Desri; Kartini, Tina; Martaseli, Evi (Universitas Dian Nuswantoro, 2023)
The purpose of this research is to determine the financial performance and soundness of cooperatives from the aspects of capital, aspects of productive asset quality, aspects of liquidity and aspects of independence and growth. This research was conducted using a qualitative method with a descriptive approach. The data collection method used by the author is the method of observation, interviews, documentation, and triangulation related to the performance and health of cooperatives in the Al-Ikhlas Cooperative. Based on the research results obtained, the performance and health of cooperatives in the Al-Ikhlas Cooperative fluctuates every year.